A high-stability silicon oxide lithium-ion battery negative electrode material and preparation method thereof

By forming Cr-MOF coating on the surface of silicon oxide powder and adhering carbon nanotubes, a high-temperature carbonized layer and a fluorinated carbon layer are formed, the problem of the decline in stability caused by the prone to agglomeration of nano silicon oxide is solved, and the preparation of the negative electrode material of high-stable silicon oxide lithium-ion battery is achieved, and the cycle stability of the battery is improved.

CN119315019BActive Publication Date: 2025-03-04ANHUI UNIV +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411866635.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-04
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Nano-silicon oxide is prone to agglomeration, and is prone to uneven mixing when mixed with carbon materials, resulting in a decrease in the stability of the negative electrode material.

Method used

By forming Cr-MOF coating in situ on the surface of the silicon oxide powder, and attaching carbon nanotubes to the Cr-MOF, the carbon layer formed by high-temperature carbonization coats the silicon oxide powder and the fixed carbon nanotubes, and then the carbon fluoride layer formed by fluorination by fluorine gas is obtained to obtain a highly stable silicon oxide lithium-ion battery negative electrode material.

Benefits of technology

This method reduces the agglomeration of silicon oxide powder, improves the stability of the negative electrode material, reduces the expansion rate of silicon oxide, and improves the cycle stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-stable silicon oxide lithium ion battery negative electrode material and a preparation method thereof, comprising the following steps: hydrothermally reacting modified silicon oxide micropowder and chromium nitrate nonahydrate to obtain MOF / silicon oxide composite powder, mixing the powder with carbon nanotubes to obtain a to-be-carbonized powder, and then carbonizing the to-be-carbonized powder in a tubular furnace and then fluorinating the powder with fluorine gas to obtain the high-stable silicon oxide lithium ion battery negative electrode material. The preparation method of the invention reduces the agglomeration of silicon oxide powder by in-situ generating Cr-MOF coating on the surface of silicon oxide powder, and heats and carbonizes carbon nanotubes uniformly after attaching the carbon nanotubes to the Cr-MOF, so that the carbonized layer formed by the carbon nanotubes at high temperature is solidified, has a high degree of bonding with the carbon layer and silicon oxide, and synergizes with the fluorinated carbon formed by fluorination with fluorine gas, thereby improving the stability of the silicon oxide lithium battery negative electrode material, reducing the expansion rate of silicon oxide, and improving the cycle stability of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of inorganic non-metallic materials, and specifically relates to a highly stable silicon oxide lithium ion battery negative electrode material and a preparation method thereof. Background Art

[0002] Compared with silicon (Si), silicon dioxide (SiO) materials have smaller volume expansion and better long cycle performance as negative electrode materials for lithium-ion batteries, and are also low in cost. Although the volume expansion rate of silicon dioxide is much smaller than 300% of silicon negative electrode materials, the expansion rate of 160% still causes serious stability problems for silicon dioxide materials. Carbon materials have good electrical conductivity, high elastic modulus, high tensile strength and large elastic strain capacity, such as graphite, carbon nanotubes, graphene, etc. SiO composite carbon materials can significantly stabilize their electrochemical properties, such as SiO / C nanospheres, graphene / SiO, SiO / C core-shell nanomaterials, etc. Carbon coating can prevent SiO from direct contact with the electrolyte, avoid direct side reactions between SiO electrodes and electrolytes to form unstable solid-phase electrolyte interface films, and carbon coating can also improve the conductivity of silicon dioxide. On the other hand, as a buffer layer, the carbon layer can effectively buffer the structural tension and deformation of the active SiO material during charge and discharge, thereby reducing the expansion rate.

[0003] However, nano-silicon oxide is easy to agglomerate and is prone to uneven mixing when mixed with carbon materials, resulting in a decrease in the stability of the negative electrode material.

[0004] Patent CN112028078A discloses a method for improving the stability of silicon oxide negative electrode materials for lithium batteries, wherein fluoride is decomposed to form fluorine in the gas phase and reacts with Li to uniformly form a lithium fluoride film on the surface of the silicon oxide negative electrode, thereby increasing the safety of pre-lithiation, improving chemical stability and reducing electrolyte corrosion to the silicon oxide matrix; however, using lithium fluoride as a thin film to coat the silicon oxide surface greatly increases the amount of lithium used and increases the cost of the battery, and lithium fluoride has poor mechanical properties and cannot reduce the expansion rate of the silicon oxide negative electrode, resulting in poor stability of the silicon oxide negative electrode. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of how to prepare lithium ion negative electrode materials by carbon-coated silicon oxide and improve the stability of the negative electrode materials, and to provide a highly stable silicon oxide lithium ion battery negative electrode material and a preparation method thereof.

[0006] The present invention obtains a highly stable silicon oxide lithium-ion battery negative electrode material by uniformly coating Cr-MOF on silicon oxide powder, attaching carbon nanotubes on Cr-MOF, coating the silicon oxide powder and fixing the carbon nanotubes with a carbon layer formed by high-temperature carbonization, and then fluorinating the carbon layer with fluorine gas.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A method for preparing a highly stable silicon oxide lithium ion battery negative electrode material comprises the following steps:

[0009] Step 1: In a reaction kettle, the modified silicon oxide powder and chromium nitrate nonahydrate are stirred and mixed in N,N-dimethylacetamide, and then the temperature is raised to 110-120° C. to react for 20-24 hours, and after cooling, the precipitate is collected by centrifugation, washed, and vacuum dried to obtain MOF / silicon oxide composite powder;

[0010] Step 2: Stirring the MOF / silicon dioxide composite powder and carbon nanotubes in a 10-15wt% sodium alginate aqueous solution for 2-3h, washing the precipitate after centrifugation, and vacuum drying to obtain a powder to be carbonized;

[0011] Step 3: In a tubular furnace, the powder to be carbonized is heated to 750-800°C under nitrogen protection for 5-6 hours at a heating rate of 5°C / min, then cooled to 250-350°C, a mixed gas of nitrogen and fluorine is introduced for 4-5 hours, and after cooling, the powder is crushed, ground and sieved to obtain a highly stable silicon oxide lithium-ion battery negative electrode material;

[0012] The volume ratio of nitrogen to fluorine in the mixed gas is 4-5:5-6.

[0013] Furthermore, in step 1, the usage ratio of modified silicon oxide powder, chromium nitrate nonahydrate and N,N-dimethylacetamide is 3-5g:2-3g:50-60mL.

[0014] Furthermore, in step 2, the usage ratio of MOF / silicon dioxide composite powder, carbon nanotubes and 10 wt % sodium alginate aqueous solution is 3-5 g: 0.3-0.5 g: 30-40 mL.

[0015] Further, the modified silicon oxide powder is prepared by the following steps:

[0016] In a reaction kettle, 4,4',4''-tricarboxylic acid triphenylamine, N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are stirred and mixed in deionized water for 1-2 hours, and then aminated silicon dioxide micropowder is added and stirred to react for 20-24 hours. After centrifugation, the precipitate is washed and vacuum dried to obtain modified silicon dioxide micropowder.

[0017] Furthermore, the usage ratio of 4,4',4''-triphenylamine tricarboxylate, N-hydroxysuccinimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, deionized water and ammoniation of silicon dioxide micropowder is 1-1.5 g: 1-1.5 g: 2-3 g: 100-150 mL: 3-5 g.

[0018] Further, the ammoniation of silicon dioxide powder is prepared by the following steps:

[0019] The pretreated silicon oxide powder is dispersed in deionized water, γ-aminopropyltriethoxysilane is added, stirred and reacted at 70-80° C. for 8-10 hours, centrifuged and the precipitate is washed, and vacuum dried to obtain aminated silicon oxide micropowder.

[0020] Furthermore, the dosage ratio of the pretreated silicon oxide powder, deionized water and γ-aminopropyltriethoxysilane is 8-10 g: 100-120 mL: 0.5-1 g.

[0021] Further, the pretreated silicon oxide powder is prepared by the following steps:

[0022] The silicon oxide powder is subjected to high-energy ball milling at room temperature at a rotation speed of 200-400 rpm for 10-12 hours to obtain silicon oxide coarse powder. The silicon oxide coarse powder is mixed with the acid mixture and then heated to 70-80°C and stirred at 60-80 rpm for 36-48 hours. After centrifugation, the precipitate is collected and washed, and vacuum dried to obtain pretreated silicon oxide powder.

[0023] Furthermore, the usage ratio of silicon oxide coarse powder to acid mixture is 1-2g:5-7mL, and the acid mixture is prepared by mixing hydrofluoric acid, hydrochloric acid and concentrated sulfuric acid in equal molar ratios.

[0024] Beneficial effects of the present invention:

[0025] The preparation method of the present invention generates a Cr-MOF coating in situ on the surface of silicon oxide powder, thereby reducing the agglomeration of silicon oxide powder, and uniformly attaches carbon nanotubes to the Cr-MOF and then heats and carbonizes the carbon nanotubes, so that the carbon nanotubes are solidified by the carbonization layer formed at high temperature on the basis of uniform bonding, have a high degree of bonding with the carbon layer and silicon oxide, and synergistically act with the fluorinated carbon formed by fluorination with fluorine gas, thereby improving the stability of the negative electrode material of silicon oxide lithium battery, reducing the expansion rate of silicon oxide, and improving the cycle stability of the lithium ion battery.

[0026] The high-stability silicon oxide lithium ion battery negative electrode material prepared by the invention is prepared by acidifying the surface of silicon oxide and then modifying it by ammoniation with a silane coupling agent, using the amino groups on the surface of aminated silicon oxide micropowder to evenly combine with the carboxyl groups on the ligand 4,4',4''-triphenylamine tricarboxylate of Cr-MOF, so that Cr-MOF is evenly generated and coated on the surface of aminated silicon oxide powder, and carbon nanotubes are evenly composited on the MOF / silicon oxide composite powder through the reaction of the carboxyl groups on the surface of MOF / silicon oxide composite powder and the hydroxyl groups on the surface of carbon nanotubes, and during high-temperature carbonization, not only the carbon nanotubes are solidified in the carbon layer, but also the carbon layer is more evenly coated on the surface of the aminated silicon oxide powder, so as to obtain the silicon oxide lithium ion battery negative electrode material with low expansion rate and high stability. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1: A method for preparing a highly stable silicon oxide lithium ion battery negative electrode material, comprising the following steps:

[0029] S1. The silicon oxide powder passed through a 300-mesh sieve was subjected to high-energy ball milling with zirconium oxide balls at room temperature at a rotation speed of 200 rpm for 10 hours to obtain silicon oxide coarse powder. The silicon oxide coarse powder was mixed with an acid mixture at a solid-liquid ratio of 1 g:5 mL, and then the temperature was raised to 70°C and stirred at 60 rpm for 36 hours. The acid mixture was prepared by mixing hydrofluoric acid, hydrochloric acid and concentrated sulfuric acid in equal molar ratios. After centrifugation, the precipitate was collected and washed with deionized water, and vacuum dried at 70°C to obtain pretreated silicon oxide powder. 8 g of the pretreated silicon oxide powder was dispersed in 100 mL of deionized water, 0.5 g of γ-aminopropyltriethoxysilane was added, and the reaction was stirred at 70°C for 8 hours. The precipitate was collected by centrifugation, washed with ethanol and deionized water, and vacuum dried at 70°C to obtain aminated silicon oxide micropowder.

[0030] S2. In a reaction kettle, 1 g of 4,4',4''-triphenylamine tricarboxylate, 1 g of N-hydroxysuccinimide and 2 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were stirred and mixed in 100 mL of deionized water for 1 h, and then 3 g of aminated silica powder was added and stirred for reaction for 20 h. After centrifugation, the precipitate was washed with deionized water and anhydrous ethanol, and vacuum dried at 70°C to obtain modified silica powder.

[0031] S3. In a reactor, 3 g of modified silicon oxide powder and 2 g of chromium nitrate nonahydrate were stirred and mixed in 50 mL of N,N-dimethylacetamide, and then heated to 110° C. for reaction for 20 h. After cooling, the precipitate was collected by centrifugation and washed with deionized water and anhydrous ethanol, and then vacuum dried at 70° C. to obtain MOF / silicon oxide composite powder.

[0032] S4. 3 g of MOF / silicon dioxide composite powder and 0.3 g of carbon nanotubes were stirred in 30 mL of 10 wt % sodium alginate aqueous solution for 2 h, and the precipitate was washed with deionized water after centrifugation, and vacuum dried at 70° C. to obtain the powder to be carbonized.

[0033] S5. In a tubular furnace, the powder to be carbonized is heated to 750°C under nitrogen protection for 5 hours at a heating rate of 5°C / min, then cooled to 250°C, and a mixed gas of nitrogen and fluorine is introduced for 4 hours, with a volume ratio of nitrogen to fluorine of 4:5. After cooling, the powder is crushed, ground and sieved to obtain a highly stable silicon oxide lithium-ion battery negative electrode material.

[0034] Embodiment 2: A method for preparing a highly stable silicon oxide lithium ion battery negative electrode material, comprising the following steps:

[0035] S1. The silicon oxide powder passed through a 300-mesh sieve was subjected to high-energy ball milling with zirconium oxide balls at room temperature at a rotation speed of 300 rpm for 11 hours to obtain a coarse silicon oxide powder. The coarse silicon oxide powder was mixed with an acid mixture at a solid-liquid ratio of 1.5 g:6 mL, and then the temperature was raised to 75° C. and stirred at 70 rpm for 42 hours. The acid mixture was prepared by mixing hydrofluoric acid, hydrochloric acid and concentrated sulfuric acid in equal molar ratios. After centrifugation, the precipitate was collected and washed with deionized water, and vacuum dried at 75° C. to obtain a pretreated silicon oxide powder. 9 g of the pretreated silicon oxide powder was dispersed in 110 mL of deionized water, 0.75 g of γ-aminopropyltriethoxysilane was added, and the reaction was stirred at 75° C. for 9 hours. The precipitate was collected by centrifugation, washed with ethanol and deionized water, and vacuum dried at 75° C. to obtain aminated silicon oxide micropowder.

[0036] S2. In a reaction kettle, 1.25 g of 4,4',4''-triphenylamine tricarboxylate, 1.25 g of N-hydroxysuccinimide and 2.5 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were stirred and mixed in 125 mL of deionized water for 1.5 h, and then 4 g of aminated silica powder was added and stirred for 22 h. After centrifugation, the precipitate was washed with deionized water and anhydrous ethanol, and vacuum dried at 75°C to obtain modified silica powder.

[0037] S3. In a reactor, 4 g of modified silicon oxide powder and 2.5 g of chromium nitrate nonahydrate were stirred and mixed in 55 mL of N,N-dimethylacetamide, and then heated to 115° C. for reaction for 22 h. After cooling, the precipitate was collected by centrifugation and washed with deionized water and anhydrous ethanol, and then vacuum dried at 75° C. to obtain MOF / silicon oxide composite powder.

[0038] S4. 4 g of MOF / silicon dioxide composite powder and 0.4 g of carbon nanotubes were stirred in 35 mL of 12.5 wt% sodium alginate aqueous solution for 2.5 h, and the precipitate was washed with deionized water after centrifugation, and vacuum dried at 75° C. to obtain the powder to be carbonized.

[0039] S5. In a tubular furnace, the powder to be carbonized was heated to 775°C under nitrogen protection for 5.5 hours at a heating rate of 5°C / min, then cooled to 300°C, and a mixed gas of nitrogen and fluorine was introduced for 4.5 hours, with a volume ratio of nitrogen to fluorine of 4.5:5. After cooling, the powder was crushed, ground and sieved to obtain a highly stable silicon oxide lithium-ion battery negative electrode material.

[0040] Embodiment 3: A method for preparing a highly stable silicon oxide lithium ion battery negative electrode material, comprising the following steps:

[0041] S1. The silicon oxide powder passed through a 300-mesh sieve was subjected to high-energy ball milling with zirconium oxide balls at room temperature at a rotation speed of 400 rpm for 12 hours to obtain silicon oxide coarse powder. The silicon oxide coarse powder was mixed with an acid mixture at a solid-liquid ratio of 2g:7mL, and then the temperature was raised to 80°C and stirred at 80rpm for 48 hours. The acid mixture was prepared by mixing hydrofluoric acid, hydrochloric acid and concentrated sulfuric acid in equal molar ratios. After centrifugation, the precipitate was collected and washed with deionized water, and vacuum dried at 80°C to obtain pretreated silicon oxide powder. 10g of the pretreated silicon oxide powder was dispersed in 120mL of deionized water, 1g of γ-aminopropyltriethoxysilane was added, and the reaction was stirred at 80°C for 10 hours. The precipitate was collected by centrifugation, washed with ethanol and deionized water, and vacuum dried at 80°C to obtain aminated silicon oxide micropowder.

[0042] The large number of mesoporous structures formed after silicon oxide is etched by the acid mixture can not only stabilize the electrode material by reducing the mechanical stress generated by lithiated silicon oxide, but also enhance the electrochemical kinetics. It is also beneficial to the surface modification and grafting of γ-aminopropyltriethoxysilane on the silicon oxide powder, so that the surface of the silicon oxide micropowder contains amino groups.

[0043] S2. In a reaction kettle, 1.5 g of 4,4',4''-triphenylamine tricarboxylate, 1.5 g of N-hydroxysuccinimide and 3 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were stirred and mixed in 150 mL of deionized water for 2 h, and then 5 g of aminated silica powder was added and stirred for reaction for 24 h. After centrifugation, the precipitate was washed with deionized water and anhydrous ethanol, and vacuum dried at 80°C to obtain modified silica powder.

[0044] S3. In a reaction kettle, 5 g of modified silicon oxide powder and 3 g of chromium nitrate nonahydrate were stirred and mixed in 60 mL of N,N-dimethylacetamide, and then heated to 120° C. for reaction for 24 h. After cooling, the precipitate was collected by centrifugation and washed with deionized water and anhydrous ethanol, and then vacuum dried at 80° C. to obtain MOF / silicon oxide composite powder.

[0045] By utilizing the reaction between 4,4',4''-tricarboxylic acid triphenylamine and the amino groups on the surface of aminated silicon oxide, 4,4',4''-tricarboxylic acid triphenylamine is grafted and coated on the surface of aminated silicon oxide. Then, using 4,4',4''-tricarboxylic acid triphenylamine as a ligand, Zr-MOF is generated in situ on the surface of aminated silicon oxide, so that Zr-MOF coats the aminated silicon oxide and reduces the agglomeration effect between silicon oxides.

[0046] S4. 5 g of MOF / silicon dioxide composite powder and 0.5 g of carbon nanotubes were stirred in 40 mL of 15 wt% sodium alginate aqueous solution for 3 h, and the precipitate was washed with deionized water after centrifugation, and vacuum dried at 80° C. to obtain the powder to be carbonized.

[0047] The carbon nanotubes are composited on the MOF / silicon oxide composite powder by utilizing the reaction between the carboxyl groups on the surface of the MOF / silicon oxide composite powder and the hydroxyl groups on the surface of the carbon nanotubes. Under the adhesion of sodium alginate, the powders to be carbonized are more firmly bonded.

[0048] S5. In a tubular furnace, the powder to be carbonized is heated to 800°C under nitrogen protection for 6 hours at a heating rate of 5°C / min, then cooled to 350°C, and a mixed gas of nitrogen and fluorine is introduced for 5 hours, with a volume ratio of nitrogen to fluorine of 5:6. After cooling, the powder is crushed, ground and sieved to obtain a highly stable silicon oxide lithium-ion battery negative electrode material.

[0049] The MOF ligands and sodium alginate in the MOF / silicon oxide composite powder are carbonized in a tubular furnace to generate a carbon layer on the surface of silicon oxide, covering the silicon oxide. At the same time, the carbonization is used to fix the carbon nanotubes in the carbon layer covering the surface of silicon oxide. The composite carbon nanotubes help to maintain a complete conductive network in the negative electrode material of the battery after long-term circulation, help to uniformity of the lithiation process, and can reduce local volume expansion. The carbon layer formed by the carbonization of MOF uses the MOF structure as a template and has a large number of nanopores. Under the fluorination of fluorine gas, the obtained MOF-derived fluorinated carbon layer has good anti-expansion ability, which reduces the expansion volume of silicon oxide.

[0050] Comparative Example 1: The difference from Example 1 is that silicon oxide powder is used to replace the aminated silicon oxide powder to prepare a highly stable silicon oxide lithium ion battery negative electrode material.

[0051] Comparative Example 2: The difference from Example 1 is that, without going through S2 and S3, 1 g of 4,4',4''-triphenylamine tricarboxylate, 1 g of N-hydroxysuccinimide, 2 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 2 g of chromium nitrate nonahydrate were stirred and mixed in a reactor in 50 mL of N,N-dimethylacetamide, and then the temperature was raised to 110°C for reaction for 20 hours. After cooling, the precipitate was collected by centrifugation and washed with deionized water and anhydrous ethanol. After vacuum drying at 70°C, it was mechanically stirred and mixed with 3 g of aminated silicon oxide micropowder to obtain MOF / silicon oxide composite powder.

[0052] The MOF / silicon oxide composite powder is used to prepare a highly stable silicon oxide lithium ion battery negative electrode material.

[0053] Comparative Example 3: The difference from Example 1 is that the MOF / silicon oxide composite powder prepared in Comparative Example 2 is used to replace the powder to be carbonized to prepare a highly stable silicon oxide lithium ion battery negative electrode material.

[0054] The high-stability silicon oxide lithium ion battery negative electrode material prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was prepared into battery electrodes for performance testing. The high-stability silicon oxide lithium ion battery negative electrode material, conductive graphite and polyacrylic acid were stirred and mixed in a mass ratio of 6:3:1, and then coated on a copper foil with a coating thickness of 100 μm. The electrode sheets were dried in a vacuum oven at 110°C for 12 h, and electrode sheets were obtained after punching. 2025 button batteries were assembled with lithium sheets as counter electrodes. The electrolyte used a silicon-based negative electrode material electrolyte (1 mol / LLiPF6, EC:DEC=1:1, 10% FEC), and the diaphragm was made of PP / PE / PP material. The battery was subjected to a constant current charge and discharge test, and the measured voltage range was 0.005-2V. The first cycle was activated at a low current density of 0.02C, and then a long cycle performance test was performed at a current density of 0.1C to test the initial capacity and first efficiency of the battery, and the capacity retention rate after 500 cycles. The results are shown in Table 1:

[0055] Table 1 Results of battery first efficiency and long cycle efficiency retention

[0056]

[0057] As can be seen from Table 1, the batteries prepared from the high-stability silicon oxide lithium-ion battery negative electrode materials obtained in Examples 1 to 3 of the present invention can still maintain a cycle capacity retention rate of more than 82% after 500 cycles, indicating that the battery negative electrode material of the present invention has good stability, a small expansion rate of the electrode material during the cyclic charge and discharge process, and a high number of cycles; in Comparative Example 1, since silicon oxide is not aminated, the bonding degree between silicon oxide powder and 4,4',4''-triphenylamine tricarboxylate is low, and the generated MOF material cannot be wrapped on the surface of silicon oxide. Because the MOF / silicon oxide composite powders are unevenly mixed during mechanical mixing, the stability of the obtained high-stability silicon oxide lithium-ion battery negative electrode material is worse than that of Examples 1 to 3; because carbon nanotubes are not added to Comparative Example 3, the first efficiency is lower than that of Comparative Example 2, and the capacity retention rate after 500 cycles is also lower, indicating that the addition of carbon nanotubes improves the stability of the high-stability silicon oxide lithium-ion battery negative electrode material.

[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a highly stable silicon oxide lithium ion battery negative electrode material, characterized in that: The steps include: Step 1: In a reaction kettle, the modified silicon oxide powder and chromium nitrate nonahydrate are stirred and mixed in N,N-dimethylacetamide, and then the temperature is raised to 110-120° C. to react for 20-24 hours, and after cooling, the precipitate is collected by centrifugation, washed, and vacuum dried to obtain MOF / silicon oxide composite powder; Step 2: Stirring the MOF / silicon dioxide composite powder and carbon nanotubes in a 10-15wt% sodium alginate aqueous solution for 2-3h, washing the precipitate after centrifugation, and vacuum drying to obtain a powder to be carbonized; Step 3: In a tubular furnace, the powder to be carbonized is heated to 750-800°C under nitrogen protection for 5-6 hours at a heating rate of 5°C / min, then cooled to 250-350°C, a mixed gas of nitrogen and fluorine is introduced for 4-5 hours, and after cooling, the powder is crushed, ground and sieved to obtain a highly stable silicon oxide lithium-ion battery negative electrode material; The volume ratio of nitrogen to fluorine in the mixed gas is 4-5:5-6; The modified silicon oxide powder is prepared by the following steps: In a reaction kettle, 4,4',4''-tricarboxylic acid triphenylamine, N-hydroxysuccinimide and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride are stirred and mixed in deionized water for 1-2 hours, and then aminated silicon dioxide micropowder is added, stirred and reacted for 20-24 hours, and the precipitate is washed after centrifugation, and vacuum dried to obtain modified silicon dioxide micropowder; The ammoniation silicon dioxide powder is prepared by the following steps: The pretreated silicon oxide powder is dispersed in deionized water, γ-aminopropyltriethoxysilane is added, stirred and reacted at 70-80° C. for 8-10 hours, centrifuged and the precipitate is washed, and vacuum dried to obtain aminated silicon oxide micropowder.

2. The method for preparing a highly stable silicon oxide lithium ion battery negative electrode material according to claim 1, characterized in that: The usage ratio of the modified silicon oxide powder, chromium nitrate nonahydrate and N,N-dimethylacetamide in step 1 is 3-5g:2-3g:50-60mL.

3. The method for preparing a highly stable silicon oxide lithium ion battery negative electrode material according to claim 1, characterized in that: In step 2, the usage ratio of the MOF / silicon dioxide composite powder, carbon nanotubes and sodium alginate aqueous solution is 3-5 g: 0.3-0.5 g: 30-40 mL.

4. The method for preparing a highly stable silicon oxide lithium ion battery negative electrode material according to claim 1, characterized in that: The dosage ratio of the 4,4',4''-tricarboxylic acid triphenylamine, N-hydroxysuccinimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, deionized water and ammoniation of silicon dioxide micropowder is 1-1.5g: 1-1.5g: 2-3g: 100-150mL: 3-5g.

5. The method for preparing a highly stable silicon oxide lithium ion battery negative electrode material according to claim 1, characterized in that: The usage ratio of the pretreated silicon oxide powder, deionized water and γ-aminopropyltriethoxysilane is 8-10 g: 100-120 mL: 0.5-1 g.

6. The method for preparing a highly stable silicon oxide lithium ion battery negative electrode material according to claim 1, characterized in that: The pretreated silicon oxide powder is prepared by the following steps: The silicon oxide powder is subjected to high-energy ball milling at room temperature at a rotation speed of 200-400 rpm for 10-12 hours to obtain silicon oxide coarse powder. The silicon oxide coarse powder is mixed with the acid mixture and then heated to 70-80°C and stirred at 60-80 rpm for 36-48 hours. After centrifugation, the precipitate is collected and washed, and vacuum dried to obtain pretreated silicon oxide powder.

7. The method for preparing a highly stable silicon oxide lithium ion battery negative electrode material according to claim 6, characterized in that: The usage ratio of the silicon oxide coarse powder to the acid mixture is 1-2 g:5-7 mL, and the acid mixture is prepared by mixing hydrofluoric acid, hydrochloric acid and concentrated sulfuric acid in equal molar ratios.

8. A highly stable silicon oxide lithium ion battery negative electrode material, characterized in that: The material is prepared by the method for preparing the high-stability silicon oxide lithium-ion battery negative electrode material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for improving stability of silicon monoxide negative electrode material of lithium battery

    CN112028078A

  • SiO@Mg / C composite material as well as preparation method and application thereof

    CN113659141A

  • Silicon monoxide / carbon nanotube composite material and application thereof in negative electrode of lithium ion battery

    CN115893425A